If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10t + -4 = -8 + 9t Reorder the terms: -4 + -10t = -8 + 9t Solving -4 + -10t = -8 + 9t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-9t' to each side of the equation. -4 + -10t + -9t = -8 + 9t + -9t Combine like terms: -10t + -9t = -19t -4 + -19t = -8 + 9t + -9t Combine like terms: 9t + -9t = 0 -4 + -19t = -8 + 0 -4 + -19t = -8 Add '4' to each side of the equation. -4 + 4 + -19t = -8 + 4 Combine like terms: -4 + 4 = 0 0 + -19t = -8 + 4 -19t = -8 + 4 Combine like terms: -8 + 4 = -4 -19t = -4 Divide each side by '-19'. t = 0.2105263158 Simplifying t = 0.2105263158
| -45=6x+9 | | (.75)(c)+(.40)(600-c)=380.00 | | 5n=2n+30 | | 55=2l+2(7) | | 1/2/4 | | 2n-9=11 | | 5+t=13+9 | | (1/2)/4 | | 3/2x+2/3x=13 | | 5+11x=86 | | 1x+2+2x=3+1 | | Q=x+y+zfory | | 6x+133=103-6x | | 6x+13=103-6x | | 3sqr(x+5)=2sqr(7-2x) | | 3w+9=2w-8 | | 11x=-x-24 | | 2x+x+1=4x-18 | | 4ln(x+4)=-4 | | 1.7-2.3=4.5z-3.5z-0.2 | | 9x-65=7x+4 | | 11d+6=8d+21 | | x+6.3=2.9 | | 3b+b=66.76 | | 4ln(x+4)=20 | | -6.4-2.1=-0.8v+3.5 | | 14(v+3)-2v=4(3v+2)-16 | | 6b+b=245 | | 8=-8u+19 | | -7/8v=-2/5 | | 3x^2+kx+4=0 | | 3e/2=9 |